Human rights and the problems of an interventionist approach: a debate between Waldron and Raz - Borges Machado, Ayrton (Universidad Hemisferios, 2025)
This article analyzes how the consideration of harsh realities in describing human rights practices can undermine both their suitability and the normativity of a human rights theory. The main argument is that Joseph Raz's theory, by failing to examine the content of human rights, offers a distorted account grounded in sovereign interventionism, without addressing the difficult realities associated with such interventions. For example, Raz overlooks the selectivity of sovereign interventions and the hidden interests that often motivate them. The critique of Raz's theory centers on two key issues: first, his methodological failure to incorporate real-world conditions, which results in an idealized portrayal of interventionism; and second, his disregard for the debate over the content of human rights, which is essential to establish their normative basis. This critique is developed through the human rights theory of Jeremy Waldron, who highlights the normative challenges and potential dangers of relying on interventionism to define the content of human rights. The article begins with an analysis of the methodological shortcomings in Raz's theory, continues with a critique of his interventionist stance, and concludes with Waldron's objections to Raz's approach.